Village Fund Management Strategy in Realized Sustainable Development Goals in Suci Village, Panti District, Jember Regency - Ardhiarisca, Oryza; Putri Andini, Dessy; Rina Wijayanti, Rahma; Harkat, Avisenna; Eka Puspita Ansori, Adelia; Hanip, Muhammad; Anisa, Siti (International Journal of Studies in Social Sciences and Humanities, 2026)
Global development challenges can be addressed through a global action plan, also known as the Sustainable Development Goals (SDGs). Each village must have precise program plans aligned with the SDGs to help achieve global development goals. This study aims to determine the strategic plan implemented by the Suci Village Government, Panti District, Jember Regency, to achieve the Sustainable Development Goals (SDGs). The method used in this study is a descriptive qualitative approach. The data sources are primary and secondary. Primary data was obtained from interviews and observations. While secondary data was obtained from documentation. Data were collected through interviews, observations, and documentation. Secondary data in the form of RPJMDes, Budget Realization Reports, Selayang Pandang Potensi Desa Suci, and Peraturan menteri Dalam Negeri No. 20 Tahun 2018. Data validity was tested through source and technique triangulation. The study results indicate that Suci Village has implemented village financial management in accordance with applicable regulations. In implementing the SDGs, several programs support them, such as direct cash assistance (BLT), stunting prevention, and waste banks. The strategy used in village management is quite good, as it emphasizes the evaluation process to ensure effective planning in accordance with the SDGs' development objectives, taking into account village conditions and partnerships.